Bisphenol B Exposure Disrupts Mouse Oocyte Meiotic Maturation in vitro Through Affecting Spindle Assembly and Chromosome Alignment - Zhang, Shou-Xin; Ding, Zhi-Ming; Ahmad, Muhammad Jamil; Wang, Yong-Sheng; Duan, Ze-Qun; Miao, Yi-Liang; Xiong, Jia-Jun; Huo, Li-Jun (Frontiers in Cell and Developmental Biology, 2020)
Bisphenol B (BPB), a substitute of bisphenol A (BPA), is widely used in the polycarbonate plastic and resins production. However, BPB proved to be not a safe alternative to BPA, and as an endocrine disruptor, it can harm the health of humans and animals. In the present study, we explored the effects of BPB on mouse oocyte meiotic maturation in vitro. We found that 150 μM BPB significantly compromised the first polar body extrusion (PBE) and disrupted the cell cycle progression with meiotic arrest. The spindle assembly and chromosome alignment were disordered after BPB exposure, which was further demonstrated by the aberrant localization of p-MAPK. Also, BPB exposure increased the acetylation levels of α-tubulin. As a result, the spindle assemble checkpoint (SAC) was continuously provoked, contributing to meiotic arrest. We further demonstrated that BPB severely induced DNA damage, but the ROS and ATP production were not altered. Furthermore, the epigenetic modifications were changed after BPB exposure, as indicated by increased K3K9me3 and H3K27me3 levels. Besides, the pattern of estrogen receptor α (ERα) dynamics was disrupted with a mass gathering on the spindle in BPB-exposed oocytes. Our collective results indicated that exposure to BPB compromised meiotic maturation and damaged oocyte quality by affecting spindle assembly and chromosome alignment, acetylation of α-tubulin, DNA damage, epigenetic modifications and ERα dynamics in mouse oocytes.